(untitled) (Gaceta de Ciencias Veterinarias, 2016)
Artisan white cheeses represent a potential risk to cause foodborne illness, due to poor sanitary conditions processing; routinely using unpasteurized Milk makes these products become in vehicles for infectious pathogens. In order to evaluate the physical, chemical and bacteriological quality of fresh artisan cheeses, applying methodology established in Venezuelan COVENIN, 32 samples were analyzed from eight artisanal cheese making production units (UP) milk included in the Dairy Development Integrated Program (PIDEL) in Manzanita, Buría parish, Lara state. The data were statistically evaluated by ANOVA (P<0,05) and differences by Tukey test. Analysis of physicochemical characteristics (pH, humidity, acidity, chlorides, fat and protein) showed significant differences among the UP, attributable to manufacturing process. According to its consistency, cheeses are classified as firm/semi-hard and according to fat content in semi-fat (UP I, VIII) and fatty (UP II, III, IV, V, VI, VII). Also, significant variation (P<0.05) was checked in the bacteriological quality indicators: aerobic mesophilic (6.14±0.01 to 8.44±0.44 log UFC/g), total coliforms (4.30±0.00 to 7.09±0.85 log NMP/g), fecal coliforms (3.68±0.04 to 6.73±0.80 log NMP/g) and Escherichia coli (1.08±2.15 to 5.69±0.58 log NMP/g). Specific pathogens Staphylococcus aureus (0.00±0.00 to 6.99±0.82 log CFU/g) was identified and its evidenced absence of Salmonella sp. According to microbiological criteria, cheeses studied showed poor hygienic-sanitary quality; therefore, they are considered unfit for human consumption due to represent a latent risk of poisoning for the consumer.